Laser spectroscopy of caesium dimers - Butcher, L; Butcher, Louise Sara (1997)
﻿ We have obtained spectra of 10 vibrational bands of the Cs2 (2)3∏u ← ϰ3∑+9 system. The molecules were formed in a supersonic free jet expansion, and were excited by light from a single mode CW dye laser. The total laser induced fluorescence was measured at 90° to the incident light and molecular beam, using a photomultiplier. Using a slit system to image a selected part of the interaction region, we have reduced the Doppler width to about 350MHz. We have been able to resolve the discrepancy between the different vibrational band positions given in two previous papers. Our vibrational bands show broad rotational contours, but we have not been able to resolve individual rotational lines. We have also obtained rotationally resolved spectra of the bandhead region of 22 vibrational bands of the Β1∏9 ← X1∑+u system. We found that the frequencies of the bandheads agreed with the bandhead positions deduced from the Dunham coefficients of a previous work. We have developed a theoretical model of the rotational structure and intensity distribution, taking into account optical pumping and the small solid angle subtended by the detector. By fitting this model to the experimental spectrum of the v' = 3,u∿ = 0 band using least squares optimization, we were able to extract rotational constants and line positions. We found that these line positions were in good agreement with those from the previous work. We have discussed how such spectroscopic data may be used in a determination of the s-wave scattering length of caesium, and we have reviewed the validity of the scattering length and other pararneterisations of low energy Cs-Cs interactions.